KAJIAN LABORATORIUM PENGGUNAAN ASPAL STARBIT E-55 MODIFIKASI POLIMER PADA ASPHALT CONCRETE WEARING COURSE (AC-WC) DITINJAU DARI DURABILITAS DAN INDIRECT TENSILE STRENGTH - , DAMIANUS KANS P.; , Ir. Latif Budi Suparma, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The conventional asphalt road has almost been considered fail to serve the transportation needs. It is indicated by the occurrence of premature damage which is caused by vehicle load and climate. Starbit E-55, the polymer modified bitumen, is formulated to meet the requirement of transport development. Considering those needs, it is important to investigate the feasibility level of that modified bitumen as an alternate asphalt instead of the conventional one. This research began with the measurement of the propertyâs value of hard layered AC-WCâs starbit E-55, then comparing the result to 60/70 penetration of Pertaminaâs asphalt. The next step is then, to determine the converted valueâs level so as to be close to the Pertaminaâs value (60/70 penetration). This step is conducted by applying durability and ITS tests on the mixture. Result of the tests showed that hard layered AC-WCâs starbit E-55 has better characteristic at 5,7% optimum level asphalt and 6,4% of Pertaminaâs asphalt (60/70 penetration). Starbit E-55 converted level within hard-layered ACWC is 5,6%. The performance testâs result on immersion with variance of 1, 3, 5, 7 and 14 days shows that durability value of Starbit E-55 AC-WC has better performance. During the process, Starbit E-55 required 15,38% higher energy consumption.